2017
DOI: 10.1002/jbm.a.36199
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility assessment of cyclic olefin copolymers: Impact of two additives on cytotoxicity, oxidative stress, inflammatory reactions, and hemocompatibility

Abstract: This work reports the biocompatibility evaluation of cyclic olefin copolymers (COC) as candidates for implantable medical devices. The focus was to establish the influence of two major additives (antioxidant and lubricant) on the overall biocompatibility. The cytotoxicity was evaluated according to ISO 10993-5 guidelines using L929 fibroblasts, HUVEC, and THP-1-derived macrophages. Oxidative stress (ROS, GSH/GSSG, and SOD analysis) and pro-inflammatory cytokines (Il-6 and TNF-α secretion) were quantified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…In vitro cytotoxicity of the fibers was assayed according to ISO 10993 part 5 guidelines 3 (Bernard et al, 2017). Extract was prepared by the incubation of 0.2 g of each fiber with 1 ml of Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 100 mg/ml penicillin, and 100 mg/ml streptomycin for 48 h at 37°C.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…In vitro cytotoxicity of the fibers was assayed according to ISO 10993 part 5 guidelines 3 (Bernard et al, 2017). Extract was prepared by the incubation of 0.2 g of each fiber with 1 ml of Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 100 mg/ml penicillin, and 100 mg/ml streptomycin for 48 h at 37°C.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…14 Different additives have already been shown to have an effect on cytotoxicity and inflammation. 15 In this article, we show that different COP materials have varying degrees of biocompatibility with human skin cell types. We have found that these differences are not obvious from standard cytotoxicity testing methods as described in USP <87> 16 and EU ISO 10993-5, 17 but can be shown by the assessment of inflammation and differentiation markers in human cells in vitro.…”
Section: Introductionmentioning
confidence: 89%
“…However, the different compositions and monomers that make up commercially available medical grade polymers have raised questions about biocompatibility testing of these materials . Different additives have already been shown to have an effect on cytotoxicity and inflammation …”
Section: Introductionmentioning
confidence: 99%
“…52 COPs have been explored as promising candidates with regards to biocompatibility and material hemocompatibility. 53 And it has been demonstrated that the hemocompatibility of COPs can be significantly increased with various additives and surface modification techniques. [53][54][55] Polymethyl Methacrylate PMMA, is an amorphous plastic with 99% light transmission and scratch resistance.…”
Section: Glassmentioning
confidence: 99%
“…53 And it has been demonstrated that the hemocompatibility of COPs can be significantly increased with various additives and surface modification techniques. [53][54][55] Polymethyl Methacrylate PMMA, is an amorphous plastic with 99% light transmission and scratch resistance. 56 Light transmission is essential in devices requiring microscopy or other optical end points.…”
Section: Glassmentioning
confidence: 99%